Borreria apodiensis (rubiaceae: spermacoceae), a new species from ceará and Rio Grande do norte, Brazil - Bezerra de Souza, Elnatan (2016)
Fil: Bezerra de Souza, Elnatan. Universidade Estadual Vale do Acaraú; Brazil.